Pendidikan Berbasis Lingkungan Sebagai Media Pembelajaran PAI di Sekolah Alam Johor Islamic Green School - Rahma Nadira Br. Munte; Dinda Valiza; Yoshy Randa Siregar; Rosyid Fauzan Hasibuan (PT. Pusmedia Group Indonesia, 2023)
A natural school is a place of learning that uses the environment as a learning medium that helps students see directly the conditions that occur in the field. This research discusses the environment as a learning medium at the Johor Islamic Green School Nature School which focuses on the concept of natural schools, PAI learning in natural schools and the successes and obstacles found in natural schools. This research methodology uses qualitative research by visiting the research site directly. The techniques used in this research are observation, interviews and documentation. The research results show that the Johor Islamic Green School Alam School uses the environment as the main medium in the learning process. The PAI lesson material at this school is also in accordance with the curriculum at schools in general. With this natural school, students will be able to develop their potential by utilizing the environment as a learning medium and be able to achieve the goals of the learning process. Keywords: Environmental Education; Islamic Education Learning Media; Nature School.